Study on the Efficacy of Durva Siddha Ghrita Gandusha in Management of Pittaja Mukhapaka - Menon, Sudeep; Chakma, Haben; Patil, Dhananjay; Patil, Anuja; Pawar, Rohit; Buduru, Mounika; Khandagale, Sagar (International Journal of Ayurvedic Medicine, 2026)
Pittaja Mukhapaka (Aphthous Ulcer) is an inflammatory condition of the oral mucosa that compromises oral comfort and interferes with routine activities. Its prevalence has increased due to lifestyle factors such as tobacco chewing and smoking. In Ayurveda (the ancient Indian system of medicine), Gandusha (therapeutic gargling) is considered a prime measure for maintaining oral health (Mukha Swasthya). The present study was undertaken to evaluate the therapeutic efficacy of this classical formulation. A single-group clinical study was conducted on 32 randomly selected participants diagnosed with Pittaja Mukhapaka (Aphthous Ulcer). The intervention involved Durva Siddha Ghrita Gandusha administered for 7 days. Assessments were recorded on the 0th and 7th days to note differences in clinical outcomes, while the 2nd and 5th days were specifically observed for any adverse drug reactions or complications. A post-treatment follow-up was carried out on the 9th day. In addition, literary data were reviewed from Ayurvedic Samhitas (classical texts), modern texts, and prior research to substantiate the findings. The results demonstrated significant relief in inflammation and discomfort, highlighting the role of Gandusha (therapeutic gargling) in enhancing local circulation, facilitating drug absorption through the oral mucosa, and promoting oral health. The study concludes that Durva Siddha Ghrita Gandusha is an effective upakrama (therapeutic procedure) in managing Pittaja Mukhapaka (Aphthous Ulcer), offering a simple, non-invasive and holistic approach to oral care.